‘Ibadah camp: a cross-faculty tool in transforming leaders of a higher education institution - Ismail, Yusof; Mhd. Sarif, Suhaimi; Azan, Zaliza (Pusat Pengembangan Integrasi Ilmu Naqli & Aqli (PIINA), 2017)
Tawhid-oriented transformation program, called ‘Ibadah camp, has been institutionalized to reinforce awareness to execute the roles, duties, responsibility and accountability of faculty members. Annual ‘Ibadah camps enable the leaders of a Higher Education Institution (HEI) to review the valued-based, Qalb-guided transformational leadership performance before planning for strategic actions to address the deficiencies. Various modules of the program may be linked to the Tawhidic paradigm that incorporates its two strategic thrusts, i.e., carrying out everyone’s roles as servant and vicegerent of Allah, respectively. The two-day and one-night ‘Ibadah Camp comprised tazkirah, recitation, memorization, and commentaries of Qur’an, outreach outing simulation, sport activities, review of leadership performance, and plan for strategic actions. The various modules are associated with four elements of transformational leadership - individualized consideration, intellectual stimulation, inspirational motivation and idealized influence. By using self-awareness as individual’s mechanism of development and action, the study argues that leaders of the higher education institution will be to attain sustainable competitive advantage. Personal interviews with selected top level (academic) managers and faculty members of the higher education institution in this study revealed that the existing modules of ‘Ibadah camp are not able to attain the expected outcome due to lack of institutional and individual support. The informants suggested that top leadership of the institution must subscribe wholeheartedly to Qalb-guided transformation leadership to give it a competitive advantage.